Synergic Usage of Pistia stratiotes sp., Eichhornia crassipes sp., Typha angustifolia sp., and Lepironia Articulata sp. Plants for Sewage Treatment via Phytoremediation Technology - Nurul Farah Anisa, Hairolnizam; Suryati, Sulaiman; Abdul Syukor, Abd Razak; Nadzirah, Mohd Mokhtar; Nadiah, Mokhtar; Azrina, Abd Aziz; Chin, Khor Bee (Bentham Open, 2024)
Introduction: Domestic wastewater management is challenging on a worldwide level. The discharge of a large amount of nitrogen and phosphate from sewage accelerates pollution can lead to reduced oxygen levels, excessive algal blooms, the expansion of aquatic weed plants, and the destruction of the aquatic environment. As a result, the right wastewater treatment is required prior to discharge into natural water bodies in order to prevent contamination and fulfill the wastewater acceptable limits established by the government and environmental protection agencies. For Previous studies, most of the research is carried out in a controlled environment within a small time frame. Phytoremediation offers a viable alternative by harnessing the natural capabilities of plants to enhance the degradation and removal of pollutants in sewage. Aims: The objective of this study is to evaluate the phytoremediation performance using Pistia stratiotes sp., Eichhornia Crassipes sp., Typha angustifolia sp., and Lepironia Articulata sp. in treating real domestic wastewater. Methods: The phytoremediation system conducted continuous treatment at the Sewage Treatment Plant (STP) effluent at Selangor, Malaysia. To the best of our knowledge there are no studies conducted on the phytoremediation plant in real STP using 4 types of aquatic plants in a row to achieve a high percentage removal of pollutants. This research observation was conducted by collecting data every 2 weeks for 4 consecutive months including the maintenance terms. In terms of pollutant removal, the phytoremediation system showed the highest removal efficiency in all tested parameters. Results: The highest removal efficiency recorded for biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS) and ammoniacal nitrogen (AN) were 68.38%, 70.95%, 59.21% and 25.00%, respectively. Conclusion: Following the guidelines of the Environmental Quality (Sewage Effluent) Regulation 2009 Malaysia, synergic usage of the aquatic plant had successfully achieved Standard A for sewage discharge after applying the phytoremediation technology while it has been proven that the environmentally friendly technologies can reduce the risk of water pollution by using the selected plant and may solve the water shortage with a cost-effective and efficient solution to wastewater treatment.